Dual-energy CT-based Assessment of the Trabecular Bone in Vertebrae - Wesarg, S.; Kirschner, M.; Becker, M.; Erdt, M.; Kafchitsas, K.; Khan, M. F. (Methods of Information in Medicine, 2012)
Background: Osteoporosis can cause severe fractures of bone structures. One important indicator for pathology is a lowered bone mineral density (BMD) – conventionally assessed by dual-energy X-ray absorptiometry (DXA). Dual-energy CT (DECT) – being an alternative that is increasingly used in the clinics – allows the computation of the spatial BMD distribution.Objectives: Using DECT, the trabecular bone of vertebrae is examined. Several analysis methods for revealing the bone density distribution as well as appropriate visualization methods for detecting regions of lowered BMD are needed for computer-assisted diagnosis (CAD) of osteoporosis. The hypothesis that DECT is better suited than DXA for the computation of local BMD is investigated.Methods: Building on a model of the interaction of X-rays with bone tissue, novel methods for assessing the spatial structure of the trabecular bone are presented. CAD of DECT image data is facilitated by segmenting the regions of interest interactively and with an Active Shape Model, respectively. The barycentric space of fractional volumes is introduced as a novel means for analyzing bone constitution. For 29 cadaver specimens, DECT as well as DXA has been examined. BMD values derived from both modalities are compared to local force measurements. In addition, clinical data from two patients who underwent DECT scanning for a different reason is analyzed retrospectively.Results: A novel automated delineation method for vertebrae has been successfully applied to DECT data sets. It is shown that localized BMD measurements based on DECT show a stronger linear correlation (R2 = 0.8242, linear regression) to local force measurements than density values derived from DXA (R2 = 0.4815).Conclusions: DECT based BMD assessment is a method to extend the usage of increasingly acquired DECT image data. The developed DECT based analysis methods in conjunction with the visualization provide more detailed information for both, the radiologist and the orthopedist, compared to standard DXA based analysis.
Keywords: Osteoporosis; computer-assisted diagnosis; dual-energy CT; statistical shape model; visualization